The Emergence of a Hybrid Public Sphere in Myanmar: Implications for Democratisation. Issue 1 (May 2021) - Middleton, Carl; Win, Tay Zar Myo
Abstract: Myanmar was under a military government for almost six decades, during which time the state maintained an 'authoritarian public sphere' that limited independent civil society, mass media and the population's access to information. In 2010, Myanmar held flawed elections that installed a semi-civilian government and established a hybrid governance regime, within which civil, political and media freedoms expanded while the military's influence remained significant. In this paper, we examine 'hybrid governance at work' in the 'hybrid public sphere', that holds in tension elements of an authoritarian and democratic public sphere. The boundaries of these spheres are demarcated through legal means, including the 2008 military-created Constitution, associated judicial and administrative state structures and the actions of civil society and community movements toward political, military and bureaucratic elite actors. We develop our analysis first through an assessment of Myanmar's political transition at the national level and, then, in an empirical case of subnational politics in Dawei City regarding the planning of the electricity supply. We suggest that the hybrid public sphere enables discourses—associated with authoritarian popularist politics in Myanmar—that build legitimacy amongst the majority while limiting the circulation of critical discourses of marginalized groups and others challenging government policies. We conclude that for substantive democracy to deepen in Myanmar, civil society and media must actively reinforce the opportunity to produce and circulate critical discourse while also facilitating inclusive debates and consolidating legislated civil, political and media freedoms. On 1 February 2021, shortly after this article was finalized, a military coup d'état detained elected leaders and contracted the post-2010 hybrid public sphere, including constraining access to information via control of the internet and mass media and severely limiting civil and political rights.